Application of RSSI-based differential location model of temperature measurement in grain depot - Gao Jinhui; Liu Hongjie; Wu Xuebing (Dianzi Jishu Yingyong, 2018)
In the traditional grain depot, the indoor location accuracy of the temperature measurement nodes depends on a large number of beacon nodes, which brings great inconvenience to practical engineering applications. To simplify the application model, a differential location model is established according to the distance attenuation curve characteristics of RSSI(Received Signal Strength Indication). Moreover, a positioning method—based on RSSI differential location model of the grain temperature measurement node was proposed. The model adopts dynamic beacon nodes, and determines the nearest unknown node from the beacon node according to the RSSI value, and finally locates all the nodes. Experiments show that the temperature measurement nodes based on the RSSI differential location model do not need additional placement of beacon nodes, which can reduce the random error of the environment and the positioning accuracy is higher than that of the traditional ranging location model.